Is Competition Law an Impediment to CSR? - Dubbink, Wim (Journal of business ethics, 2008)
This paper provides an empirical case study of the relationship between corporate social responsibility (CSR) and the new competition regulation in the Netherlands. The leading question in this case study is whether the new institutional arrangement has allowed for the possibility that reasonable exceptions can be made to the principle that inter-firm cooperation is prohibited. That is to say: does the new institutional arrangement allow for the possibility of `well organized but not `perfect’ markets’? The investigation focuses on the Netherlands, which constitutes an exemplary case as the Dutch are committed to both strengthen the competitiveness of the market and allow for exceptions on behalf of non-economic values such as CSR. The authors expect that the Dutch context will prevent a doctrinal and categorical rejecting of any good argument to make an exception to the rule that inter-firm cooperation must be prohibited.